Penilaian ke atas program bantuan pekerja (EAP) di telekom Malaysia Berhad - Noraini, Zakaria. (Universiti Malaysia Sarawak, (UNIMAS), 2003)
The main purpose of this study is to identify the perception of EAP practitioners towards the effectiveness of Employee Assistance Program in Telekom Malaysia Berhad (TMB). The aim of this study is to determine the opinion from the EAP practitioner to improve EAP at the TMB. Questionnaires were used to obtain data from 25 EAP practitioners in TMB. The data for this study were processed and analyzes by using a statistical package version 11.0. The study show that the EAP practitioner have problem in the support from top management and time management. In conclusion, the above research hat identify the opinion from respondent such as cooperation from top management, more activities about EAP, further study in counseling program, free selection of practitioner, training, recompile the task of EAP practitioner.